2017
DOI: 10.1038/cddis.2017.398
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional tumor cell growth stimulates autophagic flux and recapitulates chemotherapy resistance

Abstract: Current preclinical models in tumor biology are limited in their ability to recapitulate relevant (patho-) physiological processes, including autophagy. Three-dimensional (3D) growth cultures have frequently been proposed to overcome the lack of correlation between two-dimensional (2D) monolayer cell cultures and human tumors in preclinical drug testing. Besides 3D growth, it is also advantageous to simulate shear stress, compound flux and removal of metabolites, e.g., via bioreactor systems, through which cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 72 publications
(79 reference statements)
3
36
0
1
Order By: Relevance
“…In addition to blocking entry of free CQ into cells, the acidic extracellular microenvironment triggers activation of the transcription factor TFEB that induces lysosomal biogenesis. 264 In many cell types, though, especially in normal macrophage cells, TFEB is mutually antagonistic to STAT3 activity, and would thereby limit the protection of a tumor by macrophages. Deregulated TFEB leads to metabolic reprogramming of the cancer microenvironment.…”
Section: Feasibility Of Treating Malignant Tumors With Cq: Strengths mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to blocking entry of free CQ into cells, the acidic extracellular microenvironment triggers activation of the transcription factor TFEB that induces lysosomal biogenesis. 264 In many cell types, though, especially in normal macrophage cells, TFEB is mutually antagonistic to STAT3 activity, and would thereby limit the protection of a tumor by macrophages. Deregulated TFEB leads to metabolic reprogramming of the cancer microenvironment.…”
Section: Feasibility Of Treating Malignant Tumors With Cq: Strengths mentioning
confidence: 99%
“…263 In vitro, cancer cell autophagy and TFEB activity can be modeled in three-dimensional growth conditions. 264 In many cell types, though, especially in normal macrophage cells, TFEB is mutually antagonistic to STAT3 activity, and would thereby limit the protection of a tumor by macrophages. 265 It was shown that TFEB is activated and translocated to the nucleus via inhibition of mammalian target of rapamycin complex by CQ.…”
Section: Feasibility Of Treating Malignant Tumors With Cq: Strengths mentioning
confidence: 99%
“…The study of drug distributions and effects on downstream pathways via metabolomics approaches has successfully been used to predict antitumour cytotoxic responses by the analysis of extracellular metabolites in cancer patients . These metabolomic studies have been extended to three‐dimensional (3D) cell culture studies, whereby the environment recapitulates the drug resistance seen in vivo , and have further shown that metabolomic profiles may predict the malignant potential of cells grown in 3D cell culture …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, to flow within the blood vessels, the interstitial flow moves in all directions. The studies on flow‐induced shear stress showed its influence on the cell molecular signaling, gene expression, cell cycle, autophagy, and chemotherapy resistance (Bingel et al, ; Chang et al, ; Hakkinen, Harunaga, Doyle, & Yamada, ; Ham et al, ; Massai et al, ; Santoro, Lamhamedi‐Cherradi, Menegaz, Ludwig, & Mikos, ). Accordingly, to develop an appropriate in vitro model of cancer that would more closely imitate the pathophysiological conditions, at least three requirements should be implemented such as the cells heterogeneity, three‐dimensionality, and the stress forces.…”
Section: Introductionmentioning
confidence: 99%